Mammalian chitotriosidase and its role in innate immunity - Hall, Andrew J. (2009)
The main aim of this thesis was to characterize mammalian chitotriosidase in terms of its function in innate immunity. This was achieved using several different approaches. In terms of gene expression, it was demonstrated that chitotriosidase is highly expressed in human peripheral blood monocyte-derived macrophages and can be induced further by β-glucan-containing PAMPs. This suggests that the enzyme may be involved specifically in anti-fungal immunity. Furthermore, chitotriosidase activity was detected in neutrophil pellets and the supernatants of cells treated with prolactin (consistent with its putative role in immune modulation) and the degranulating compound fMLP.